Household Socioeconomic Status and Antenatal Care Utilization Among Women in the Reproductive-Age - Sui, Yubing; Ahuru, Rolle Remi; Huang, Kaishan; Anser, Muhammad Khalid; Osabohien, Romanus (Frontiers in Public Health, 2021)
The study examined the effect of household socioeconomic status and other socio-demographic characteristics on antenatal care (ANC) utilization among 819 women within the reproductive ages across eight rural communities in Delta State, Southern part of Nigeria. Characteristics of the women were described using simple proportion and frequency. The chi-square test was used to examine factors that were significantly associated with a minimum of four (≥4) and eight (≥8) antenatal care contacts, which were respectively in line with the focused ANC and WHO's new guideline. The multivariable logistic regression was used to examine the determinants of a minimum of four and eight ANC. Statistical analyses were set at 5%. The results showed that 31.4% (257/819) and 2.2% (18/819) of mothers, respectively, made ≥ 4 and ≥ 8 ANC contacts in the course of their last pregnancies. According to the results, the odds for reporting 4≥ and ≥ 8 ANC improved with both wealth and educational attainment. Distance to the health center and cost are barriers to maternal care utilization and they reduce the odds for undertaking ≥ 4 and ≥8 ANC contacts. Women on higher media exposure were more likely to undertake ≥ 4 and ≥8 ANC contacts, and those on the highest media exposure were more likely to undertake ≥8 ANC contacts. Financing maternal care through health insurance and free maternal care significantly improves the odds to undertake ≥ 4 and ≥ 8 ANC contacts. Intervention programs should be designed to improve access to maternal care services and should expand education opportunities for mothers, improve household socioeconomic conditions, and encourage enrolment in health insurance and free maternal care in the study area.